Effect of Consumption Values on Consumer Satisfaction and Brand Commitment: Investigating Functional, Emotional, Social, and Epistemic Values in the Running Shoes Market - Furukawa, Hiroyasu; Matsumura, Koki; Harada, Susumu (International Review of Management and Marketing, 2019)
Firms can acquire sustainable competitive advantages by managing brand relationships and consumption values. However, previous studies do not compare consumption value with consumer satisfaction and brand commitment. Consumption value theory postulates that functional, emotional, social, and epistemic values enhance brand relationships. However, the most effective element of consumption values on consumer satisfaction or brand commitment is different. Specifically regarding running shoes, this article empirically compares functional, emotional, social, and epistemic values with consumer satisfaction and brand commitment. Using a mediated–moderation regression model, this article collected 844 Japanese samples from a marathon in Kobe, Japan, and tested how multiple consumption values affected consumer satisfaction and brand commitment, moderated by age. The results show that consumption values except epistemic value have positive effects on consumer satisfaction and brand commitment. In particular, this article uncovers the moderating effect of age in social values and consumer satisfaction. Specifically, social values affect consumer satisfaction when consumers are under 39 years old. This paper also found that functional value and social value have the strongest effect on consumer satisfaction and brand commitment, respectively, compared with other values. Contravening consumption value theory, our data suggests that epistemic value impedes brand commitment. Keywords: Consumption Values Theory, Consumer Satisfaction, Brand Commitment, Running Shoes JEL Classifications: M10, M21, M31 DOI: https://doi.org/10.32479/irmm.8713